IoT Based Well-organized Hostel Power Consumption and Attendance Administration System. Issue 1 (February 2021) - Geetha, V; Anbumani, V; Selvi, T; Sindhuja, C S; Vanathi, S
Abstract: Most of the educational institutions in India are with the conservative follows for monitoring their resources precisely hostel facilities. In this project, two major issues namely energy conservation and monitoring of hostel attendance are considered. Now a days the power consumption by the educational institutions is more than 2 billion units as per the survey held in 2015. Energy demand is one of the increasing burdens for government and it is increasing exponentially in the recent scenario. Energy conservation can be the greatest key for rising energy demand. In this regard, power saving is a vital matter and it is more serious in hostels as some irresponsible students who leave the room without switching OFF the lights and fans. Another issue with today's hostel maintenance is student's attendance and their in/out time. Conventional system follows camera facilities. But many miserable incidents have happened to the students especially girls when they had a long travel to their hometown. Hence by means of well-organized hostel administration system with RFID reader, fingerprint sensor, PIR sensor is designed to work under two modes namely Manual Mode and Automatic Mode and provides solution for these two issues.